2018
DOI: 10.3389/fpsyg.2018.01733
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Approximate Number System in Different Mathematics Skills Across Grades

Abstract: Although approximate number system (ANS) has been found to predict mathematics ability, it remains unclear if both aspects of ANS (symbolic and non-symbolic estimation) contribute equally well to mathematics performance and if their contribution varies as a function of the mathematics outcome and grade level. Thus, in this study, we examined the effects of both aspects of ANS on different mathematics skills across three grade levels. Three hundred eleven children (100 children from kindergarten, 107 children f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
(99 reference statements)
0
18
1
1
Order By: Relevance
“…To date, the majority of studies on the relationship between PASS scores with reading and mathematics performance have been conducted either with typically developing children (e.g., Cai et al, 2018;Das et al, 2008;Georgiou et al, 2015;Kroesbergen et al, 2010;Papadopoulos, 2001;Wang et al, 2012) or with children experiencing reading or mathematics disabilities (e.g., Cai et al, 2013;Das et al, 2007;Iglesias-Sarmiento & Deaño, 2011;Joseph et al, 2003;Kroesbergen et al, 2003). For example, in a study with Grade 3 English-speaking children, Das et al (2007) reported that the probability of a child being a poor reader if his or her standard score in successive processing was below 80 was 0.76.…”
Section: Pass Processes and Superior Reading Or Mathematics Performmentioning
confidence: 99%
“…To date, the majority of studies on the relationship between PASS scores with reading and mathematics performance have been conducted either with typically developing children (e.g., Cai et al, 2018;Das et al, 2008;Georgiou et al, 2015;Kroesbergen et al, 2010;Papadopoulos, 2001;Wang et al, 2012) or with children experiencing reading or mathematics disabilities (e.g., Cai et al, 2013;Das et al, 2007;Iglesias-Sarmiento & Deaño, 2011;Joseph et al, 2003;Kroesbergen et al, 2003). For example, in a study with Grade 3 English-speaking children, Das et al (2007) reported that the probability of a child being a poor reader if his or her standard score in successive processing was below 80 was 0.76.…”
Section: Pass Processes and Superior Reading Or Mathematics Performmentioning
confidence: 99%
“… Bonny and Lourenco (2012) found that preschoolers (3–5 years of age) with more precise number representations were generally more mathematically competent, as assessed by a standardized test of early math achievement. However, results in this area vary ( Feigenson et al, 2013 ; Kroesbergen and Leseman, 2013 ) and not all studies have found significant links between non-symbolic number performance and mathematics achievement in children (e.g., Vanbinst et al, 2012 ; Kroesbergen and Leseman, 2013 ; Sasanguie et al, 2013 ). These differences in research findings could be related to the kind of tasks used to assess comparison skills.…”
Section: Introductionmentioning
confidence: 97%
“…The ANS is a pre-linguistic cognitive system for representing and processing quantity information and has received a great deal of attention in recent years ( Dehaene, 1997 ; Cantlon et al, 2009 ; Gallistel, 2011 ; Gilmore et al, 2014 ; Leibovich et al, 2017 ; Peng et al, 2017 ; Cai et al, 2018 ; Odic and Starr, 2018 ). The ANS supports the representation and processing of different magnitudes ( Cantlon et al, 2009 ) and according to Dehaene (1997) , it is a universal system present in animals, children, and adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations